Handgrip strength and all‐cause dementia incidence and mortality: findings from the UK Biobank prospective cohort study. Issue 3 (21st April 2022) - Esteban‐Cornejo, Irene; Ho, Frederick K.; Petermann‐Rocha, Fanny; Lyall, Donald M.; Martinez‐Gomez, David; Cabanas‐Sánchez, Verónica; Ortega, Francisco B.; Hillman, Charles H.; Gill, Jason M.R.; Quinn, Terence J.; Sattar, Naveed; Pell, Jill P.; et al.
Abstract: Background: This study aimed to investigate the associations of grip strength with incidence and mortality from dementia and whether these associations differ by sociodemographic and lifestyle factors. Methods: A total of 466 788 participants of the UK Biobank (median age 56.5 years, 54.5% women). The outcome was all‐cause dementia incidence and mortality and the exposure was grip strength. Grip strength was assessed using a Jamar J00105 hydraulic hand dynamometer. Results: Excluding the first 2 years of follow‐up (landmark analysis), mean follow‐up was 9.1 years (inter‐quartile range: 8.3; 9.7) for incidence and 9.3 (inter‐quartile range: 8.7; 10.0) for mortality. During this time, 4087 participants developed dementia, and 1309 died from it. Lower grip strength was associated with a higher risk of dementia incidence and mortality independent of major confounding factors ( P  < 0.001). Individuals in the lowest quintile of grip strength had 72% [95% confidence interval (CI): 1.55; 1.92] higher incident dementia risk and 87% [95% CI: 1.55; 2.26] higher risk of dementia mortality compared with those in the highest quintile. Our PAF analyses indicate that 30.1% of dementia cases and 32.3% of dementia deaths are attributable to having low grip strength. The association between grip strength and dementia outcomes did not differ by lifestyle or sociodemographic factors. Conclusions: Lower grip strength was associated with a higher risk of all‐cause dementia incidence and mortality, independently of important confounding factors.